An arduous journey from human pluripotent stem cells to functional pancreatic β cells. Issue 1 (7th June 2017) - Loo, Larry Sai Weng; Lau, Hwee Hui; Jasmen, Joanita Binte; Lim, Chang Siang; Teo, Adrian Kee Keong
Abstract : Type 1 and type 2 diabetes are caused by a destruction and decrease in the number of functional insulin‐producing β cells, respectively; therefore, the generation of functional β cells from human embryonic stem cells and human induced pluripotent stem cells, collectively known as human pluripotent stem cells (hPSCs), for potential cell replacement therapy and disease modelling is an intensely investigated area. Recent scientific breakthroughs enabled derivation of large quantities of human pancreatic β‐like cells in vitro, although with varied glucose‐stimulated insulin secretion kinetics. In the present review, we comprehensively summarize, compare and critically analyze the intricacies of these developing technologies, including differentiation platforms, robustness of protocols, and methodologies used to characterize hPSC‐derived β‐like cells. We also discuss experimental issues that need to be resolved before these β‐like cells can be used clinically.